Age and schooling are associated with job loss in the initial months of the COVID-19 pandemic in Brazil (Research, Society and Development, 2024)
Brazil was one of the countries most affected by the social and economic crisis caused by the COVID-19 pandemic. This study aimed to verify the association between job loss and region of the country, sex, age, educational status, marital status, and parenting in Brazilian workers during the initial months of the COVID-19 pandemic. This cross-sectional online study was performed with data from workers aged 18 years or older in any economic sector and different occupations. A sociodemographic and occupational questionnaire was applied. Data collection began on June 2020 and ended on September 2020. To estimate the degree of association between job loss and the region of the country and workers’ characteristics, binomial logistic regression analysis was performed to obtain the odds ratio (OR) and confidence intervals. The sample was composed of 1319 participants and of these, 108 (8.2%) lost their jobs in the initial months of the pandemic; 51.6% were female; 53.5% were married; 42.5% reported having children; 80.7% had a complete college education. The age and educational status were associated with job loss, with younger and less educated workers being more affected by unemployment. For women, age and educational status were associated with job loss, for men only educational status showed a significant association. Young workers, mainly women, and with less educational status were the most affected by unemployment at the beginning of the pandemic in Brazil. Thus, this group of workers proved to be more vulnerable and should be prioritized by public policies.